2004
DOI: 10.1381/0960892042583879
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Hemorrhage after Laparoscopic Gastric Bypass

Abstract: Gastrointestinal hemorrhage is a potential perioperative complication after Roux-en-Y gastric bypass. The surgeon performing laparoscopic gastric bypass should understand the need for early recognition and management of this complication, as it can be lifethreatening. This paper discusses the incidence and clinical presentation of gastrointestinal hemorrhage, mechanisms for hemorrhage, management options, and possible methods of prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 10 publications
(11 reference statements)
1
58
0
3
Order By: Relevance
“…The great majority of studies reporting complications after gastric surgery did not focus on anastomotic hemorrhage. There are some reports dealing with the management of anastomotic bleeding after gastric bypass surgery for severely obese patients to whom antithrombotics were given to prevent deep venous thrombosis [14][15][16][17][18][19], but few reports have dealt with the management of anastomotic hemorrhage following gastrectomy for gastric cancer [10]. Fischer [11] reported a case of bleeding from the anastomosis using a linear stapler after gastrectomy for duodenal ulcer treated by reoperation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The great majority of studies reporting complications after gastric surgery did not focus on anastomotic hemorrhage. There are some reports dealing with the management of anastomotic bleeding after gastric bypass surgery for severely obese patients to whom antithrombotics were given to prevent deep venous thrombosis [14][15][16][17][18][19], but few reports have dealt with the management of anastomotic hemorrhage following gastrectomy for gastric cancer [10]. Fischer [11] reported a case of bleeding from the anastomosis using a linear stapler after gastrectomy for duodenal ulcer treated by reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…Umano et al [10] reported three cases of anastomotic bleeding following esophagojejunostomy or gastroduodenostomy, which were treated by endoscopic microwave coagulation therapy. In many cases of anastomotic bleeding after gastric bypass surgery, epinephrine injection and/or heater probe cauterization was used for endoscopic hemostasis [14,17,18]. Tang et al [19] reported a successful case of endoscopic hemostasis using endoclips for anastomotic bleeding after gastric bypass surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The bleeding which starts 6 hours postoperatively and is accompanied by hematocrit rate reduction is usually the evidence of continuous bleeding, in most cases requiring urgent surgical intervention. On the contrary, if gastrointestinal bleeding occurs 48 hours after surgery and hematocrit rate is not significantly changed there is no need for active surgical manipulations [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…Like any other surgical intervention, RYGB is associated with possible complications and many of them may become life threatening. Postoperative bleeding is one of such complications, its prevalence being cited as 1-4% [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation